EXPRESSING SEMANTIC CATEGORY OF VALUE WITH LEXICAL-SEMANTIC METHOD - Isakova Zilolakhon Zokirovna (Galaxy International Interdisciplinary Research Journal, 2022)
It is acknowledged that humanity’s main difference from other creatures is its highly developed intellect and the language that allows to fully express his feelings and participate in communication. In almost all languages, the most common form of information exchange is the word. Therefore, the level where the most of value relationship occurs during the exchange of information between the addresser and the addressee in communication is the lexicon.